The influence of P/As substitution in the melilite‐like Na2Co(P2–xAsx)O7 (x = 0.40 and 0.93) solid solutions. Issue 4 (1st April 2017) - Issaoui, Chokri; Chebbi, Hammouda; Guesmi, Abderrahmen
Abstract : Crystal structures of the solid solutions Na2 CoP1.60 As0.40 O7 and Na2 CoP1.07 As0.93 O7 have been determined and investigated by BVS (bond valence sum) and CHARDI (charge distribution) validation tools. The BVS model also allowed simulation of the sodium conduction pathways in the studied structural type. Abstract : To investigate the influence of P/As substitution on structures and electrical properties, e.g. the effect on material densities, two new solid P/As‐doped solutions, Na2 CoP1.60 As0.40 O7 (disodium cobalt diphosphorus arsenic heptaoxide) and Na2 CoP1.07 As0.93 O7 (disodium cobalt phosphorus arsenic heptaoxide), with melilite‐like structures have been synthesized by solid‐state reactions. Their unit‐cell parameters are in agreement with Vegard's law. The obtained structural models were investigated by the bond valence sum (BVS) and charge distribution (CHARDI) validation tools and, for the latter, the structures are described as being built on anion‐centred polyhedra. The frameworks can be described as layered and formed by [Co(P, As)2 O7 ] 2− ∞ slabs, with alkali cations sandwiched between the layers and with the interlayer spaces increased due to P/As substitution. The BVS model was extended to a preliminary simulation of the sodium conduction properties in the studied structural type and suggests that the most probable sodium conduction pathways are bidimensional, at the (002) planes.